An African slaving port and the Atlantic world : Benguela and its Hinterland - Candido, Mariana P. (Mariana Pinho), 1975- (2013)
"This book traces the history and development of the port of Benguela, the third largest port of slave embarkation on the coast of Africa, from the early seventeenth to the mid-nineteenth century. Benguela, located on the central coast of present-day Angola, was founded by the Portuguese in the early seventeenth century. In discussing the impact of the trans-Atlantic slave trade on African societies, Mariana P. Candido explores the formation of new elites, the collapse of old states, and the emergence of new states. Placing Benguela in an Atlantic perspective, this study shows how events in the Caribbean and Brazil affected social and political changes on the African coast. This book emphasizes the importance of the South Atlantic as a space for the circulation of people, ideas, and crops"--
Machine generated contents note: Acknowledgments; Introduction; 1. Contacts, competition, and copper: Benguela until 1710; 2. The rise of an Atlantic port, 1710-1850; 3. Benguela and the South Atlantic World; 4. Mechanisms of enslavement; 5. Political reconfiguration of the Benguela Hinterland, 1600-1850; 6. Conclusion.
Includes bibliographical references (pages 323-349) and index.
Keywords: Slave trade -- Africa, West -- History; HISTORY / Africa / General; Benguela (Angola) -- Economic conditions